2022
DOI: 10.1111/1744-7917.13154
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive, antimicrobial and insecticidal activities of inhibitor cystine knot peptides produced by teratocytes of the endoparasitoid wasp Cotesia flavipes (Hymenoptera: Braconidae)

Abstract: Teratocytes are specialized cells released by parasitoid wasps into their hosts. They are known for producing regulatory molecules that aid the development of immature parasitoids. We have recently reported the primary structures of cystine-rich peptides, including some containing inhibitor cystine knot (ICK) motifs, produced by teratocytes of the parasitoid Cotesia flavipes (Hymenoptera: Braconidae). ICKs are known for their stability and diverse biological functions. In this study, we produced four putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…Finally, the study of host-parasitoid interactions by an omic approach, that allows the identification of host regulation factors of parasitic origin, provides useful information and molecules of natural origin that could be used in the biological control of insect pests. Although numerous other studies are necessary, several examples of factors of parasitic that have shown insecticidal activity are reported in the literature [47,61,87] and this could be true also for T. nigriceps OPs.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the study of host-parasitoid interactions by an omic approach, that allows the identification of host regulation factors of parasitic origin, provides useful information and molecules of natural origin that could be used in the biological control of insect pests. Although numerous other studies are necessary, several examples of factors of parasitic that have shown insecticidal activity are reported in the literature [47,61,87] and this could be true also for T. nigriceps OPs.…”
Section: Discussionmentioning
confidence: 97%
“…Knottintype peptides incorporating the ICK motif demonstrate exceptional stability against heat denaturation and protein degradation. These peptides have become valuable assets in disease treatment due to their robustness [22,26,32]. Extensive investigation has revealed that this peptide class effectively displays antimicrobial, antifungal, and antiparasitic properties [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This structure is further reinforced by at least three disulfide bonds, resulting in a macrocyclic configuration through pairings like C1-C4, C2-C5, and C3-C6 [22][23][24]. Peptides with this structural configuration exhibit exceptional chemical, thermal, and proteolytic stability, presenting promising prospects for drug development and diagnostic applications [25][26][27]. Notably, their remarkable stability opens novel opportunities for oral drug delivery, unlike other protein therapies, which are typically ill-suited for oral administration due to the distinct conditions of the gastrointestinal tract.…”
Section: Of 13mentioning
confidence: 99%
“…Cotesia vestalis injects PDV particles into its hosts, causing apoptosis of host hemocytes and increasing the susceptibility of the hosts to bacterial infections [27]. The teratocytes of C. flavipes produce ICK peptides that suppress the host's cellular immunity [28]. However, comprehensive analyses of how parasitoids manipulate their hosts are largely lacking.…”
Section: Introductionmentioning
confidence: 99%